Affordability Assessment of Community Health Centre Services in Klaten Regency - Cahyoko, Fajar Dwi; Aditya, Nanda Oktarina; Darusasi, Restutita; Kurniawati, Lucky Anggi; Nurmaulid, Mitha Safira (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: The existence and affordability of community health centers play a crucial role in supporting the achievement of health development goals. Klaten Regency as one of the regions in Central Java Province has various geographical characteristics and population densities, which resulted in inequality in access to health. This study aimed to assess the affordability of community health center distribution in the Klaten Regency by 2025.Methods: This study was conducted descriptively. Secondary data were obtained from the Klaten Regency Health Profile 2023 for distribution by sub-district and Google Earth for geographic coordinates. Spatial analysis was conducted using Nearest Neighbor Analysis (NNA) to determine distribution patterns, and buffer analysis to assess service coverage. Results: The NNA produced a T-ratio of 1.54, indicating a dispersed distribution of community health centers. Buffer analysis with a 3,000-meter service radius showed that many residential areas remain outside the reach of existing facilities.Conclusion: The Klaten Regency Government should prioritize accessibility to health services through strategic mapping of health workers and facilities, providing incentives for staff in underserved areas, and optimizing health technology to improve service coverage.